Cooperative Learning Models in Improving Understanding of the Basics of Islam in Muslim Minority Areas - Muhammad Syarif Muda Hasibuan; Hasan Syukur; Imam Syabirin; Muhammad Hanif Alwan Ash-Sidiqqi; Muhammad Made Prasetya (ASSUNNAH PRESS, 2022)
The problem in Muslim minority areas is the lack of Islamic learning, so children in these areas do not have sufficient opportunities to learn Islam. One of the Muslim minority areas facing this problem is the village of Tangga Batu 1, Lake Toba. Therefore, a community service program will be carried out to introduce Islam more broadly to children, especially knowledge of Islam, and improve their ability to read the Al-Qur’an well. The method used in solving the problems that occur is the ABCD (Asset Based Community Development) method, which is an approach that wants to empower the community by starting from the assets and strengths of the community. The implementation of community service programs is direct with the community. The results of the community service program include three main things. First, learning the basics of Islam has been carried out so that many children already know the pillars of Faith and Islam well. Second, learning Iqro' runs smoothly so that children can distinguish between harf hijaiyah and long and short readings. Third, learning to improve Al-Quran reading is also carried out well so that children can read the Al-Al-Qur’an correctly, such as applying the nun sukun and mim sukun. So, after the community service program was implemented, there was a significant change in children's knowledge of Islam. They already know the basics of Islam well; their reading of harf hijaiyah is correct, and their Al-Quran reading is good.